Contribution to knowledge of the oribatid mite genus Oribatodes (Acari, Oribatida, Cepheusidae), with supplementary descriptions of two species and data on juvenile instars - Ermilov, Sergey G.; Bayartogtokh, Badamdorj (Zootaxa, 2024)
The supplementary descriptions of two species of Oribatodes (Oribatida, Cepheusidae), O. mirabilis Banks, 1895 and O. reticulatus (Sitnikova, 1979), are presented, based on adults collected from the U.S.A. and Panama, respectively. The deutonymphal and tritonymphal instars of O. mirabilis and the deutonymphal instar of O. reticulatus are described; this is the first data on juveniles of the genus. The revised generic diagnosis and an identification key to the known representatives of Oribatodes are provided. The taxonomic status of the related genus Reticulocepheus Vasiliu & Călugăr, 1977 is discussed, resulting in the following new taxonomic proposals: Oribatodes Banks, 1895 (=Reticulocepheus Vasiliu & Călugăr, 1977 syn. nov.); O. areolatus (Sitnikova, 1979) comb. nov.; O. decoui (Vasiliu & Călugăr, 1977) comb. nov.; O. grandis (Sitnikova, 1979) comb. nov.; O. mirabiloides (Jacot, 1938) comb. nov.; and O. reticulatus (Sitnikova, 1979) comb. nov. Comparative characteristics of juveniles of the different genera of Cepheusidae are given based on our own data and available literature sources.